Correlation between sowing time of maize hybrids, yield and seed moisture content at harvest on chernozem soil - Sárvári, Mihály; Futó, Zoltán (Acta Agraria Debreceniensis, 2001)
In this paper, we analysed the results of maize sowing time experiments conducted by the Department of Crop Sciences and Applied Ecology of the University of Debrecen Agricultural Sciences Centre, during the period from 1997-1999. We made the experiments at the experimental garden of DE ATC, on a chernozem soil with lime deposits.In 1997, we examined five hybrids, in 1998 six hybrids, and in 1999 three hybrids, with three sowing times. Sowing times were early (10. Apr. and 08. Apr.), optimal (25. Apr. and 28. Apr.) and late (15. May and 17. May). We examined the following standards: yield, seed moisture content at harvest, thousand kernel mass, duration of flowering, emergence time and profitability.In 1977, the emergence times, in order of sowing, were: 24, 12 and 9 days. Yields of the sowing times were the following, in mean, for the five hybrids: in the early sowing time (10. Apr.) 11,81 t/ha, in the optimal sowing time (25. Apr.) 11,67 t/ha, and in the late sowing time (15. May) 12,9 t/ha. The seed moisture content of the five hybrids at harvest was 8% less in early sowing time, than in the late sowing time. The thousand kernel mass was the biggest in late sowing time, but we could not prove any significant connection attributable to the effect of sowing time. We examinedprofitability, too. Of the five hybrids, four attained the greatest profit with the early sowing time in 1997.In 1998, the emergence times, in the order of sowing, were: 21, 10 and 11 days. Yields of the sowing times were the following, in mean, for the six hybrids: 08. Apr. 10,34 t/ha, 25. Apr. 11,02 t/ha, 15. May 11,52 t/ha. There were no significant differences between yields in 1998. The seed moisture content of the six hybrids at harvest was 7% less for the early sowing time, than for the late sowing time. In 1998, the profits were greatest for theearly and traditional sowing times.In 1999, the numbers of days from sowing to emergence were 18, 9 and 9 days, in the order of sowing times. Yields of the sowing times were the following, in mean, for the three hybrids: 13,25  t/ha, 12,51 t/ha and 12,34 t/ha, in the order of sowing times. The seed moisture content of maizes at harvest was 6% less with an early sowing time in the mean of all hybrids. In 1999, hybrid maizes gave big profits with early sowing times.Summing up the results of the three years, we can conclude that we get a significant yield increase and reduced seed moisture content at harvest if we apply the early sowing time, which can considerably increase the efficiency of maize cultivation.